2011
DOI: 10.1093/eurheartj/ehr043
|View full text |Cite
|
Sign up to set email alerts
|

Arrhythmogenic right ventricular cardiomyopathy/dysplasia on the basis of the revised diagnostic criteria in affected families with desmosomal mutations

Abstract: AimsTo evaluate arrhythmogenic right ventricular cardiomyopathy/dysplasia (ARVC/D) in affected families with desmosome mutations on the basis of the recently revised Task Force Criteria (TFC).Methods and resultsOne hundred and three consecutive carriers of pathogenic desmosome mutations and 102 mutation-negative relatives belonging to 22 families with dominant and 14 families with recessive ARVC/D were evaluated according to the original and revised TFC. Serial cardiac assessment with 12-lead, signal-averaged,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 17 publications
0
47
0
Order By: Relevance
“…Genetic studies have identified mutations in several genes associated with ARVC, including 5 desmosomal and 4 nondesmosomal genes. [5][6][7][8][9][10][11][12] Previous studies have shown that genetic identification is related to different clinical characteristics of ARVC. [13][14][15][16] However, the correlation between genotype and VA features remains unclear.…”
mentioning
confidence: 99%
“…Genetic studies have identified mutations in several genes associated with ARVC, including 5 desmosomal and 4 nondesmosomal genes. [5][6][7][8][9][10][11][12] Previous studies have shown that genetic identification is related to different clinical characteristics of ARVC. [13][14][15][16] However, the correlation between genotype and VA features remains unclear.…”
mentioning
confidence: 99%
“…Mutations in genes encoding desmosomal proteins have been identified as the causative molecular defect in more than 50% of probands. Recently, the identification of a pathogenic mutation has been incorporated into the revised diagnostic criteria for ARVC [6] , leading to a significant increase in diagnostic yield for the disease [2,9] . A pathogenic mutation is defined as a DNA alteration associated with the disease that alters or is expected to alter the encoded protein, is not observed or is rare in a large healthy control population and either alters the structure or function of the protein or has demonstrated linkage to the disease phenotype [6] .…”
Section: Discussionmentioning
confidence: 99%
“…Approximately half of all cases of ARVC are familial. The most common genetic causes of ARVC are mutations in genes encoding desmosomal proteins which lead to cell adhesion defect [2,3] . However, reduced penetrance, variable expressivity and the fact that genetic test results should be viewed as probabilistic make ARVC diagnosis a challenge for clinicians [4,5] .…”
Section: Introductionmentioning
confidence: 99%
“…This is quite evident in the recessive cardiocutaneous syndromes, which are characterized by an earlier clinical onset of cardiac involvement with a higher penetrance of complications than the autosomal-dominant form. 33 In the clinical setting, candidates for genetic test include both ARVC index cases and family members of those gene-positive. There is not yet a well-defined role for routine genetic screening to confirm a clinical diagnosis in index cases.…”
Section: Genetic Backgroundmentioning
confidence: 99%